2008
DOI: 10.18553/jmcp.2008.14.9.831
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of a Clinical Pharmacy Intervention in a Primary Care Practice in a Capitated Payment System

Abstract: BACKGROUND: There is evidence that pharmacist interventions improve clinical outcomes. The few studies that address economic outcomes (a) often report estimated instead of actual medical costs, (b) report only medication costs, or (c) have been conducted in settings that are not typical of community-based primary care.OBJECTIVES: To (a) determine whether a clinical pharmacist's recommendations to physicians regarding optimizing medication therapy are related to medical costs in capitated patients in an interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 38 publications
1
32
0
4
Order By: Relevance
“…Our intervention therefore relied on action being taken by the PCP during the office visit, potentially lessening its 21 This study included a control group for which the clinical pharmacist made recommendations for care improvement that were not disclosed to physicians. In this control group, nearly one-quarter of the concealed recommendations were enacted by physicians without pharmacist input.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention therefore relied on action being taken by the PCP during the office visit, potentially lessening its 21 This study included a control group for which the clinical pharmacist made recommendations for care improvement that were not disclosed to physicians. In this control group, nearly one-quarter of the concealed recommendations were enacted by physicians without pharmacist input.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Altavela et al (2008) found that 23.5% of drug therapy recommendations that would have been made by clinical pharmacists to physicians, but that were concealed from the physicians using a controlled research design, were adopted by the physicians anyway. 24 Also embedded in the significant questions left unanswered by research on the real effects of automated alerting systems on patient safety is rate of receipt of these messages by prescribers. Unlike an electronic prescribing system that requires an action by the prescriber at the point of care, we do not know what proportion of the mail or fax alerts were actually received and interpreted by the prescribers.…”
Section: Can Better Assessment Methods Yield Better Targeting?mentioning
confidence: 99%
“…There were net cost savings in patient care for the group as a result of these interventions. 28 Pharmacists have demonstrated clinical, humanistic and economic benefits in improving patient care for a number of chronic diseases. Pharmacists receive extensive education in identifying medication-related problems and therapeutic appropriateness (ensuring safety and efficacy) of medications.…”
Section: Future Models Benefits Of Pharmacists In Primary Carementioning
confidence: 99%